Sensory integration of children with autism spectrum disorder - Bobrova Valentina Vladimirovna; Sagadiyeva Tomiris Kanatovna (European Research Materials, 2023)
This article reveals the concept of "sensory integration" and substantiates the rationality of using the method of sensory integration for the development of a child with autistic disorders.